"This lifetime commitment": Public conceptions of disability and noninvasive prenatal genetic screening. Issue 2 (14th November 2015) - Steinbach, Rosemary J.; Allyse, Megan; Michie, Marsha; Liu, Emily Y.; Cho, Mildred K.
Abstract : Recently, new noninvasive prenatal genetic screening technologies for Down syndrome and other genetic conditions have become commercially available. Unique characteristics of these screening tests have reignited long‐standing concerns about prenatal testing for intellectual and developmental disabilities. We conducted a web‐based survey of a sample of the US public to examine how attitudes towards disability inform views of prenatal testing in the context of these rapidly advancing prenatal genetic screening technologies. Regardless of opinion toward disability, the majority of respondents supported both the availability of screening and the decision to continue a pregnancy positive for aneuploidy. Individuals rationalized their support with various conceptions of disability; complications of the expressivist argument and other concerns from the disability literature were manifested in many responses analyzed. © 2015 Wiley Periodicals, Inc.